2008
DOI: 10.1073/pnas.0810268105
|View full text |Cite|
|
Sign up to set email alerts
|

Dendritic cells in the thymus contribute to T-regulatory cell induction

Abstract: Central tolerance is established through negative selection of self-reactive thymocytes and the induction of T-regulatory cells (T R s). The role of thymic dendritic cells (TDCs) in these processes has not been clearly determined. In this study, we demonstrate that in vivo , TDCs not only play a role in negative selection but in the induction of T R s. TDCs include two conventional dendritic cell (DC) subtypes, CD8 lo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
284
3

Year Published

2010
2010
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 268 publications
(311 citation statements)
references
References 58 publications
20
284
3
Order By: Relevance
“…B cells could facilitate graft tolerance by inducing allograft-specific Tregs across an MHC barrier (57, 58), a mechanism that may be of significance in the context of graft-versus-host disease. Though the mechanism by which B cells could provide immunological tolerance to solid-organ grafts in the clinic are as yet unidentified, our data with BAFF-Tg mice suggests that B cells can accumulate within the thymus, where they can present cognate MHC-Ag complexes to engender thymic Tregs, mechanisms previously associated with DCs (5,41).…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…B cells could facilitate graft tolerance by inducing allograft-specific Tregs across an MHC barrier (57, 58), a mechanism that may be of significance in the context of graft-versus-host disease. Though the mechanism by which B cells could provide immunological tolerance to solid-organ grafts in the clinic are as yet unidentified, our data with BAFF-Tg mice suggests that B cells can accumulate within the thymus, where they can present cognate MHC-Ag complexes to engender thymic Tregs, mechanisms previously associated with DCs (5,41).…”
Section: Discussionmentioning
confidence: 86%
“…Intrathymic Treg cell selection requires cognate interactions with peptide-MHC II complexes on the surface of thymic APCs (4,41). We could show that resident thymic B cells express surface MHC II molecules, as well as the costimulatory molecules CD80 and CD86 (data not shown), indicating they have the required machinery for Treg selection.…”
Section: Thymic B Cells Provide Cognate Help For the Expansion Of Natmentioning
confidence: 87%
See 1 more Smart Citation
“…More interestingly, it has been reported that DCs can be infected by influenza viruses in vitro (30). Because of the DC function to migrate continuously into the LN but also in the thymus (15) with or without having contact and being activated by an Ag, thymic DCs play a major role in establishing tolerance by negative selection of thymocytes and induction of Tregs (45). We hypothesized that DCs are the carrier cell type for influenza viruses.…”
Section: Discussionmentioning
confidence: 99%
“…30,31 Moreover, peripheral DCs migrate to the thymus where they present peripheral antigens. 32,33 Taken together, these observations suggest that DCs participate in the maturation of T cells and the generation of FoxP3 þ Tregs in the thymus. However, the depletion of DCs does not affect thymic T-cell maturation and FoxP3 þ Treg generation, suggesting that the contribution of DCs to these processes is minimal.…”
Section: Function Of Dcs In Cns Autoimmunitymentioning
confidence: 73%